An Algorithm for Predicting the Speed of Traffic Light Violators - Iswanjono Iswanjono; Bagio Budiardjo; Kalamullah Ramli (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
The tracking of vehicles using RFID was developed consider three major problems, i.e. traffic signal timing, congestion on road and theft of vehicles. This paper describes an algorithm for predicting the speed of traffic light violators. The novel algorithm is implemented in the form of a simulation program. The traffic light system is equipped RFID reader as the main tool for identifying the vehicle’s RFID tags. In the simulation, the vehicle’s ID is generated using a random number generation. The distribution of the vehicle’s numbers is uniform and the expected number of vehicles violated the traffic light is not more than 3 % of the total number generated. The timing accuracy for speed traffic lights violator is 100 milli seconds. From the simulation conducted, the algorithm has performed as expected. It is able to predict the speed of traffic light violators ranging from 5 km/h up to 80 km/h in real-time.